Decision on the range of peak current during cryogenically assisted electric discharge machining process. (2022) - Goyal, Rachin; Kumar, Amresh; Chaitanya, Saurabh; Mohal, Sachin; Goyal, Aneesh
Abstract: In any research work, the role of preliminary experimentation to decide the range of various input parameters can never be overlooked. To commence the main experimentation a range of these parameters is selected on the basis of preliminary experiments and an in-depth literature review. The Peak Current (Ip) is considered to be the most predominant input parameter affecting the cryogenically assisted electric discharge machining (CEDM) process. In this paper, the effects of varying the peak current have been evaluated in terms of Material Removal Rate (MRR), Tool Wear Rate (TWR), Surface Roughness (SR), Aspect Ratio (AR) and Out of Roundness and the range of the peak current to be kept during CEDM of AISI D2 has been focused. The electrolytic copper has been used as tool electrode. After conducting the experiments and with the support of literature, it is proposed to keep the range of peak current from 4 A to 12 A, under given machining conditions. The Scanning electron microscope (SEM) analysis of machined workpiece were also performed and CEDM was found to be better than EDM.